Social disconnection and metabolic syndrome score among Cambodian Americans with depression. (May 2021) - Megan Berthold, S.; Bermudez-Millan, Angela; Buckley, Thomas; Buxton, Orfeu M.; Feinn, Richard; Kong, Sengly; Kuoch, Theanvy; Scully, Mary; Seng, Kagnica; Wagner, Julie
Abstract: Aims: Migrants experience social disconnection and also have high risk for metabolic syndrome (MetS). This study explored associations of social alienation, social isolation, and social support with MetS among Cambodian Americans. Methods: We conducted secondary data analysis on baseline assessments from a diabetes prevention trial for Cambodian Americans with depression and high risk for diabetes. Participants were aged 35–75, Cambodian or Cambodian-American, Khmer speaking, lived in Cambodia during the Pol Pot regime, lived in the northeastern U.S. at the time of study, endorsed elevated risk factors for diabetes and met criteria for depression by medication for depression and/or elevated depressive symptoms. They completed surveys and provided anthropometric and blood pressure measurements and fasting blood samples. Results: In multiple linear regressions, greater social alienation was associated with increased risk for MetS. The social alienation-MetS association was stronger in men than women. Associations were not better accounted for by crude indicators of social isolation such as marital status, living alone, and number of people in the household. Social support was not associated with MetS and did not buffer the deleterious association between social alienation and MetS. Conclusions : Decreasing social alienation may mitigate risk for MetS among migrant populations.